2014
DOI: 10.5296/rbm.v1i2.5091
|View full text |Cite
|
Sign up to set email alerts
|

Language Learning Strategies of Graduates for Future Employment – An Overview

Abstract: English language fluency among graduates is becoming an important capability that graduates need for employment. The industry has noted the declining level of English among Malaysian graduates thus strategies and policies need to be implemented. This paper gives an overview on three areas of literature that is pertinent to this topic: competencies and future employment, language learning strategies and supplier learning. This paper suggest that a model for capability development from the area of supply chain m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
0
2
0
1
Order By: Relevance
“…According to the graduates, it was also in line to learn English that most university students are aware of English's importance for their future employability, even though the results of their English proficiency tests are primarily poor (Abdul Kadir et al, 2015;Ranasinghe & Ranasinghe, 2012). Students and graduates valued vocabulary as the main area of English content and speaking proficiency as the English language competency.…”
Section: Figure 7 Students and Graduates' Perspectives On The English...mentioning
confidence: 99%
See 1 more Smart Citation
“…According to the graduates, it was also in line to learn English that most university students are aware of English's importance for their future employability, even though the results of their English proficiency tests are primarily poor (Abdul Kadir et al, 2015;Ranasinghe & Ranasinghe, 2012). Students and graduates valued vocabulary as the main area of English content and speaking proficiency as the English language competency.…”
Section: Figure 7 Students and Graduates' Perspectives On The English...mentioning
confidence: 99%
“…Research has shown that English language proficiency remains a crucial area of interest for English as a Foreign Language (EFL) learners in Indonesia (Nasution et al, 2020). However, there is room for improvement in their English proficiency test results (Abdul, 2015;Ranasinghe, 2012). Given that English is the international language of communication and business, proficiency becomes essential for VCD professionals, with employers valuing effective communication and teamwork skills in prospective graduate employees Coldstream (2003).…”
Section: Introductionmentioning
confidence: 99%
“…Sebagai bahasa Asing dan bahasa Internasional banyak manfaat yang akan di dapat diantaranya akan menjadi nilai tambahan bagi siswa siswi. Menurut Kadir & Noor (2015), kemampuan bahasa Inggris sangat bermanfaat untuk mendapatkan pekerjaan dikemudian hari. Lebih lanjut, Ting et al, (2017) juga menyebutkan ketika seseorang menguasai bahasa Inggris dan memiliki kemampuan komunikasi yang baik maka akan memperbesar peluang mereka dalam mendapatkan pekerjaan di masa depan.…”
Section: Pendahuluanunclassified
“…University needs to provide the relevant measures to enable undergraduates to gain the required communication skills for employment. Employers in studies by Jaafar et al (2018), Kadir and Noor (2015) blamed graduates' preference for using the Malay language in the workplace as a barrier to effective communication in English. They asserted that the wide use of Malay language in classes and lectures in some universities and peer pressure were hindrances to the English communication skills of accounting graduates at workplace.…”
Section: Introductionmentioning
confidence: 99%